Financial Performance Analysis of Company PT. Industry Jamu and Sido Muncul Tbk. In 2017-2021 Using The Financial Ratio (Journal of Business and Management, 2022)
PT. Industry Jamu and Sido Muncul, Tbk. was founded in 1951 with a simple company called Sido Muncul which means “Dreams Come True” on Jalan Mlaten Trenggalun, Semarang. Sido Muncul has several flagship products, including Tolak Angin, Tolak Linu, Kuku Bima Energi, Alang Sari Plus, Kopi Jahe Sido Muncul, Kuku Bima Kopi Ginseng, Susu Jahe, Jamu Komplit, dan Kunyit Asam. Then in 2013, Sido Muncul conducted its first IPO on the Indonesia Stock Exchange with the stock code “SIDO”. This research aims to analyze the financial performance of Sido Muncul from 2017 to 2021, using the aspect of Financial Ratio Analysis. The variables include (Current Ratio, Quick Ratio, Cash Ratio, Debt to Equity Ratio, Debt to Asset Ratio, Receivable Turnover, Inventory Turnover, Fixed Asset Turnover, Total Asset Turnover, Return on Assets, and Return on Equity). Then the results will be compared with other companies in the same industry, namely PT. Kalbe Farma, Tbk. (KLBF), PT. Kimia Farma, Tbk. (KAEF), PT. Indofarma, Tbk. (INAF), PT. Tempo Scan Pacific, Tbk. (TSPC), PT. Phapros, Tbk. (PEHA). After performing calculations using the Financial Ratio aspects, it was found that SIDO's financial performance during the 2017-2021 period was good in terms of Liquidity Ratios and Solvability Ratios, but not with Profitability Ratios and Activity Ratios because they did not meet industry ratio standards from experts.Keywords: Financial Performance, Financial Ratio, Ratio Analysis, Financial Report, Financial Ratio Analysis, Standard Ratio, PT. Industry Jamu and Sido Muncul, Tbk.